2016
DOI: 10.1016/j.celrep.2016.08.066
|View full text |Cite
|
Sign up to set email alerts
|

Parent-of-Origin DNA Methylation Dynamics during Mouse Development

Abstract: Summary Parent-specific differentially methylated regions (DMRs) are established during gametogenesis and regulate parent-specific expression of imprinted genes. Monoallelic expression of imprinted genes is essential for development suggesting that imprints are faithfully maintained in embryo and adult. To test this hypothesis, we targeted a reporter for genomic methylation to the imprinted Dlk1-Dio3 intergenic DMR (IG-DMR) to assess the methylation of both parental alleles at single cell resolution. Biallelic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 56 publications
1
22
0
Order By: Relevance
“…To test whether the dCas9-mediated DNA methylation-editing tools could be used to alter methylation in vivo we utilized a methylation sensitive reporter mouse previously generated (Fig 7A, Stelzer et al, Cell Reports , 2016, in press). In these transgenic mice, a methylation sensitive Snrpn-GFP cassette was inserted into the Dlk1-Dio3 locus to report the methylation status of its intergenic-differentially methylated region (IG-DMR).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To test whether the dCas9-mediated DNA methylation-editing tools could be used to alter methylation in vivo we utilized a methylation sensitive reporter mouse previously generated (Fig 7A, Stelzer et al, Cell Reports , 2016, in press). In these transgenic mice, a methylation sensitive Snrpn-GFP cassette was inserted into the Dlk1-Dio3 locus to report the methylation status of its intergenic-differentially methylated region (IG-DMR).…”
Section: Resultsmentioning
confidence: 99%
“…In these transgenic mice, a methylation sensitive Snrpn-GFP cassette was inserted into the Dlk1-Dio3 locus to report the methylation status of its intergenic-differentially methylated region (IG-DMR). As the IG-DMR of this locus acquires paternal methylation during spermatogenesis, the GFP reporter (IG-DMR GFP/Pat ) is constitutively repressed in heterozygous mice carrying the paternal Snrpn-GFP allele (Stelzer et al, Cell Reports , 2016, in press). As shown above the GFP reporter in the Dazl locus was activated by targeted promoter demethylation in mES cells (Fig 1).…”
Section: Resultsmentioning
confidence: 99%
“…A mouse model containing a tdTomato/GFP reporter of either the maternally or paternally expressed Dlk‐Dio3 intergenic differentially DNA‐methylated region (IG‐DMR) revealed that, whereas many cells faithfully maintained allelic expression, changes in methylation patterns were present in a tissue‐specific and cell type‐specific manner [66]. Intriguingly, neurogenic regions, such as the subventricular zone and subgranular zone of the dentate gyrus, have biallelic hypermethylation of the IG‐DMR region, suggesting tissue‐type specificity and allowing for neuronal heterogeneity [66]. DNA methylation was first thought to drive this preferential expression of genomic imprinting [67].…”
Section: Epigenetic Modificationsmentioning
confidence: 99%
“…However, these previously examined modifiers result in attenuations that are global in nature and may have off-target effects. Our results could be used to overcome this limitation since the suite of therapeutic candidates identified can be utilized as prioritized targets for somatic epigenetic editing studies [64][65][66][67] . Ultimately, our results could form the molecular foundation for developing effective interventions for deficient early maternal care in humans or be developed as new treatments for psychiatric disorders 67 .…”
Section: Discussionmentioning
confidence: 99%